Caracterização molecular e avaliação de resistência a chumbo e cádmio em bactérias isoladas de rizosferas de plantas coletadas em Santo Amaro (BA) - Souza, Adriana Fidelis Couto (2013)
In the 1960’ the mining company Plumbum Mineradora was installed in the Satate of Bahia, Brazil. This company, which produced lead ingots for 33 years, left over 400,000 tons of slag, which contained, among other pollutants, cadmium and lead. These metals are currently found in the soil surrounding the old factory, in concentrations considered highly toxic. A study was started to investigate possible bioremediation in the area with the isolation of bacteria from the rhizosphere of local plants, followed by the test in their performance in metals contaminant tolerance. Finally, identification of the bacteria was made based on molecular marker 16S rRNA. The isolation protocol was carry out using Nutrient Agar and after obtaining a pure culture. The isolates were then subjected to tests of Minimum Inhibitory Concentration (CIM). Each isolate served as a source for extraction of DNA for molecular analysis with 16S rRNA region. Among the rhizospheres collected, those from which the greatest number of species were isolated from plants with a perennial habit, among them the castor bean (Ricinus communis L.) and embaúba (Cecropia pachystachya Trécul) which together comprised approximately 38% of all species of bacteria obtained. Interestingly, from the castor bean (an exotic plant in Brazil), 2/3 of the bacteria were Gram negative, while from the embaúba (a native plant of Brazil), ¾ of the bacteria isolated were of Gram positive. Regardless of the classification of Gram, the bacteria studied showed higher tolerance to lead; 70% of Gram negative bacteria showed conspicuous morphological changes, whereas of those that were Gram positive, only 13% demonstrated. In addition, these bacteria have been identified by molecular analysis using the 16S rRNA marker. The used methodology based on analysis of parsimony and distance trees. As a result, the region 16S was able to identify only 22% of species while the remain species could only be identified to genus or to infra-generic groups. Therefore, the data suggest that the Gram negative and Gram positive bacteria have distinct mechanisms of adaptation in environments polluted by lead and cadmium and that the 16S region is not an efficient universal barcode marker, which should be used only as the first step on the identification of bacteria. Although this study does not provide a final parameter for ecological factors under consideration here, it provides an insight into the influence of the plant habitat on bacterial communites, and the role of Gram in the mechanisms of tolerance. It is hope to explore these aspects in the further studies.